Draft genome sequence of Salmonella enterica subsp. enterica Serovar gallinarum biovar pullorum strain FCAV198, a Brazilian chicken pathogen - Batista, Diego Felipe Alves [UNESP]; Freitas Neto, Oliveiro Caetano de [UNESP]; Leite, Laura Rabelo; Varani, Alessandro de Mello [UNESP]; Araujo, Flavio Marcio Gomes; Salim, Anna; Almeida, Adriana Maria de [UNESP]; Ribeiro, Simone Alves Mendes; Oliveira, Guilherme Corrêa de; Barrow, Paul A.; Berchieri Junior, Angelo [UNESP] (Genome Announcements, 2014)
Salmonella enterica subsp. enterica serovar Gallinarum biovar Pullorum is a bird-restricted pathogen which causes pullorum disease. The strain FCAV198 was isolated from a pool of chicken ovaries in Brazil, and its genome may be helpful for studies involving molecular mechanisms related to pathogenesis and other related applications.